Virulent Attack: Role-Playing Learning Media to Enhance Student’s Cognitive Learning Outcomes (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The cognitive learning outcomes of 10th-grade students at SMA Islam Malang regarding the concept of viruses are low. This is due to the perception among students that the virus concept is difficult to grasp, and the learning methods employed tend to be monotonous. Consequently, the aim of this study is to develop and assess the effectiveness of 'Virulent Attack' - a role-playing learning media adapted from the popular game Werewolf - in improving the cognitive learning outcomes of high school students in understanding the virus concept. Following the ADDIE development model, the study involved 29 X-D students from SMA Islam Malang who had no prior knowledge of the virus concept. The validation test was conducted by three experts (one material expert, one media expert, and one biology teacher) using a validation sheet questionnaire. The practicality test was carried out by students during the trial stages, and one educational practitioner provided feedback through a response questionnaire. The effectiveness test was evaluated by comparing students' pretest and posttest scores on cognitive learning outcomes, which were analyzed using the N-Gain score criteria. The findings indicate that 'Virulent Attack' is highly valid (material expert: 100%, media expert: 94.64%, biology teacher: 96.68%), practical (average score: 90.58%), and moderately effective in improving cognitive outcomes (N-Gain score: 0.66, effectiveness: 66.55%). Importantly, the game provided a positive learning experience, increased motivation, and facilitated a deeper conceptual understanding, suggesting its potential application in real-world educational contexts. These findings not only highlight the value of role-playing games in educational settings but also have practical implications for incorporating such media into biology curricula to enhance engagement and understanding.